KONTAMINASI MERKURI (Hg) DALAM ORGAN TUBUH IKAN PETEK (Leiognathus equulus) DI PERAIRAN ANCOL, TELUK JAKARTA - Riani, Etty (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Mercury (Hg) which is contained in aquatic ecosystem can enter and be accumulatedÃ‚Â to organismÃ¢â‚¬â„¢s body, like on petek fish (Leiognathus equulus). The research aimed toÃ‚Â see mercury concentration in aquatic ecosystem, to see mercury concentration in organÃ‚Â of petek fish by AAS (Atomic Absorption Spectrophotometer) and its histopathology response in organs of petek fish. The research was done at Ancol, Jakarta Bay onÃ‚Â October-December 2004. There are 16 samples of water and fish from 3 stations.The analysis result of water quality is compared by standard quality of sea water forÃ‚Â sea organism life (Kepmen LH No. 51, 2004), mercu ry concentration in fish organ isÃ‚Â compared by maximum mercury concentration in fish body by classification of PalarÃ‚Â (2004). Ancol water quality is still on normal condition. Mercury concentration in waterÃ‚Â and petek fish organs had low concentration. Gill and lever contaminated by mercuryis only in station 1 fish, but it is still on normal concentration. Histopathology of petekÃ‚Â fish gill is not abnormal, while the lever is necrosis. Water and petek fish is not a goodÃ‚Â indicator to detect mercury in aquatic ecosystem.Keywords: mercury, petek fish, water, lever, gill, histopathology, accumulation,indicator